Peculiar Operational Features of Quarter-Wave Power Supply in Electric System - G. E. Pospelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains an analysis of the operational conditions of a quarter-wave power supply in an electric system. Its applicability for the operation in electric mains and electric power transportation is shown in the paper.